Understanding Technology Trends In Education: How Artificial Intelligence Helps Learning In College And Beyond - Fauzi Fauzi; Rizky Wardhani; Guntur Arie Wibowo; Didik Cahyono; Hanifatul Rahmi (Journal Neosantara Hybrid Learning, 2024)
Technology trends have changed the educational paradigm, especially at the tertiary level. Artificial Intelligence (AI) has emerged as a way to change the learning process with the form of games in education, this will make education in higher education experience increased efficiency and effectiveness in learning. However, a deep understanding of how artificial intelligence can improve higher learning experiences and their impact after graduation is still limited. This research aims to investigate how artificial intelligence helps learning in higher education and its impact on students' career preparation after graduation. The focus is on analysis of the implementation of AI in teaching, learning, and decision-making support in higher education institutions. The research method used is literature study and content analysis. Data was collected from scientific articles, books, as well as related research reports on the use of artificial intelligence in higher education. The data is then analyzed to identify trends, benefits, and challenges associated with applying AI in educational contexts. Research results show that the use of artificial intelligence in higher education has increased the personalization of learning, increased knowledge retention, and facilitated more timely and accurate feedback. Additionally, AI also plays an important role in helping students develop skills relevant to the future job market. The conclusion of this research is that by integrating artificial intelligence into higher education, institutions can improve the quality of learning and help students be better prepared to face the challenges of an ever-changing job market. However, challenges such as technology dependency and the need for proper training for educators and students must also be addressed so that the full potential of AI in education can be realized.